Paediatric rheumatology clinic population in Southeast Asia: are we different?. (16th December 2016) - Arkachaisri, Thaschawee; Tang, Swee-Ping; Daengsuwan, Tassalapa; Phongsamart, Gun; Vilaiyuk, Soamarat; Charuvanij, Sirirat; Hoh, Sook Fun; Tan, Justin Hung Tiong; Das, Lena; Ang, Elizabeth; Lim, Wendy; Chan, Yiong Huak; et al.
Abstract : Objectives. To examine the descriptive epidemiology of the patient population referred to paediatric rheumatology centres (PRCs) in Southeast Asia (SEA) and to compare the frequency of conditions encountered with other PRC populations. Methods. A web-based Registry for Childhood Onset Paediatric Rheumatic Diseases was established in 2009 and seven PRCs in four SEA countries, where paediatric rheumatologists are available, participated in a prospective 24 month data collection (43 months for Singapore). Results. The number of patients analysed was 4038 (788 from Malaysia, 711 from the Philippines, 1943 from Singapore and 596 from Thailand). Over 70% of patients evaluated in PRCs in Malaysia, the Philippines and Thailand had rheumatic diseases (RDs), as compared with one-half of the proportion seen in Singaporean PRCs, which was similar to the Western PRC experience. Among RDs diagnosed (n = 2602), JIA was the most common disease encountered in Malaysia (41%) and Thailand (61%) as compared with systemic vasculitides in the Philippines (37%) and Singapore (35%) among which Henoch–Schönlein purpura was the most prevalent. SLE and related diseases were more common, but idiopathic pain syndrome and abnormal immunological laboratory tests were rarer than those seen in the West. JIA subtype distributions were different among countries. Among non-RDs (n = 1436), orthopaedic and related conditions predominated (21.7–59.4%). Conclusion. The frequencies of RDs seen by SEA PRCs were different from those in the West. Systemic vasculitides and SLE were common in addition to JIA. Paediatric rheumatologist availability and healthcare accessibility partially explain these observed discrepancies.